The internationalization of local currencies of emerging countries: the experience of the Mexican peso and the Chinese renminbi - Levy, Noemi (Brazilian Keynesian Review, 2018)
Globalization introduced private and structural endogenous money (private monetary debts) as the main instrument of financial capital mobilization in the international financial system. A main consequence of this feature was the internalization of emerging economies currencies unfolding two successful experiences: the foreign exchange transactions related to the Mexican peso and the Chinese renminbi. The former currency internationalized as a result of the institutional changes unfolded in the Mexican economy and it’s insertion to the North American region (NAFTA); while the latter stemmed from a government strategy to influence the worldwide economy as a result of its accelerated economic growth and increased importance in the world economy. In this paper are discussed three main themes:  the way in which emerging economies currencies internationalized; the insertion of these economies in the international market, and the divergent developments of successful currency internationalization.